Harmonious triads : physicists, musicians, and instrument makers in nineteenth-century Germany - Jackson, Myles W. (Transformations (M.I.T. Press), 2006)
An analysis of the intersection of science and music in nineteenth-century Germany: how music provided physicists with a venue for experiments as well as a cultural resource, and how physics assisted musicians in their art and musical instrument makers in.